2008
DOI: 10.1371/journal.ppat.1000155
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Mitochondria in Survival of Cryptococcus neoformans Under Low Oxygen Conditions and Tolerance to Cobalt Chloride

Abstract: Cryptococcus neoformans is an environmental fungal pathogen that requires atmospheric levels of oxygen for optimal growth. For the fungus to be able to establish an infection, it must adapt to the low oxygen concentrations in the host environment compared to its natural habitat. In order to investigate the oxygen sensing mechanism in C. neoformans, we screened T-DNA insertional mutants for hypoxia-mimetic cobalt chloride (CoCl2)-sensitive mutants. All the CoCl2-sensitive mutants had a growth defect under low o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 71 publications
2
67
0
Order By: Relevance
“…Our data and previous studies on A. fumigatus and other fungi indicated an association of functional mitochondria with the ability to adapt to low-oxygen environments (11,17,(67)(68)(69)(70). The upregulation of several respiratory genes during long-term exposure to hypoxia is also consistent with the increased production of components of the electron transport chain and oxidative phosphorylation on the proteome level (12,13).…”
Section: Discussionsupporting
confidence: 88%
“…Our data and previous studies on A. fumigatus and other fungi indicated an association of functional mitochondria with the ability to adapt to low-oxygen environments (11,17,(67)(68)(69)(70). The upregulation of several respiratory genes during long-term exposure to hypoxia is also consistent with the increased production of components of the electron transport chain and oxidative phosphorylation on the proteome level (12,13).…”
Section: Discussionsupporting
confidence: 88%
“…Hence the tubular morphology is likely to be a result of up-regulation of many candidate genes listed in Table S3. Early studies on Cryptococcus have demonstrated the importance of mitochondria in responding to hypoxic conditions and oxidative stress (30,31). We therefore propose that, after being engulfed by macrophages, the VIO strains are able to promote mitochondrial fusion to form long tubular mitochondria to more efficiently repair mtDNA damage caused by the oxidative species and hypoxic conditions present within the macrophage phagosome.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, it is possible that Galf plays a role under conditions not included in our analysis. C. neoformans is an extremely adaptable environmental yeast that can withstand a variety of harsh conditions (63)(64)(65) and is capable of living in close association with numerous organisms, including plants (66,67), birds (68,69), predatory amoebae (70), and mammals (71,72), notably humans (73,74). The cryptococcal capsule in particular is a dynamic structure whose morphology and architecture change with growth conditions (75)(76)(77) and the local environment (52,55).…”
Section: Discussionmentioning
confidence: 99%